Development of a mobile application for mathematics learning - Paievska, Diana; Bazurin, Vitaliy; Yurchenko, Yurii (My University, 2024)
Over the past four years, the educational process has undergone significant digitization and has become a reality of our present day. This rapid spread is driven by a variety of factors: the rapid advancement of digital technologies; the shift to distance learning, initially triggered by the Covid-19 pandemic, and later by the events of full- scale Russian military invasion of Ukraine; the emergence of a new generation of learners in general secondary and higher education, who better perceive bright visualized information, as well as the practical functions of the educational process aimed at developing key competencies.
Keywords: мобільний додаток; навчання математики; розробка мобільного додатку